PA-MSHA Regulates PD-L1 Expression in Hepatoma Cells. (3rd April 2023) - Wei, Hangzhi; Mao, Yudong; Zhang, Huihan; Wu, Fahong; Zhang, Youcheng
ABSTRACT: Background: Programmed death ligand 1 (PD-L1) is expressed in hepatocellular carcinoma (HCC) cells. PD-L1 function and structure are regulated through glycosylation and various signaling pathways. However, the relationship between Pseudomonas aeruginosa mannose sensitive hemagglutinin (PA-MSHA), glycosylation and PD-L1 warrants further study. In this study, we investigated the effects of PA-MSHA on the regulation of mannosyl and N-glycosylation to identify the mechanisms underlying its function. Methods: PD-L1, β-catenin, c-Myc, mannosyl, MGAT1 and mannosidase II in HCC were identified by postoperative specimens from the HCC cohort with immunohistochemistry and immunofluorescence. PA-MSHA was used to suppress tumor progression. Alterations to the expression of PD-L1, β-catenin, c-Myc, MGAT1, and mannosidase II at the gene and protein levels were detected by qRT-PCR and Western blot analysis. Soluble PD-L1 (sPD-L1) were detected using enzyme-linked immunosorbent assay. Results: Mannosyl and mannosidase II expression levels increased, whereas those of MGAT1 decreased in the HCC cells. The glycosylation-related pathway proteins, namely, β-catenin, c-Myc and PD-L1, had increased expression levels. Moreover, proliferation in the HCC cells was inhibited after PA-MSHA treatment, PD-L1 function was significantly inhibited. Transmission electron microscopy showed that PA-MSHA penetrated into the HCC cytoplasm through the cytomembrane, resulting in apoptosis. Here, PA-MSHA significantly reduced sPD-L1 expression levels in the tumor cells. Conclusions: PA-MSHA plays the role of a lectin, affecting receptors on the cytomembrane. This strain inhibits mannosyl by suppressing β-catenin signaling. We hypothesized that PA-MSHA suppresses PD-L1 by: 1. Inhibiting the glycosylation process; and 2. Suppressing β-catenin and c-Myc, thereby reducing the transcription of this protein.